The complete mitochondrial genome sequence of Dendrocopos major (Aves, Piciformes, Picidae). Issue 1 (2nd January 2019) - Park, Chang Eon; Kim, Min-Chul; Ibal, Jerald Conrad Pernites; Quang, Huy Pham; Park, Hee Cheon; Shin, Jae-Ho
Abstract: The great spotted woodpecker Dendrocopos major (Aves, Piciformes, Picidae) are the widespread woodpeckers from Eurasia and Northern Africa. The complete mitochondrial genome sequence consisted of 16, 845 base pairs (bp) encoding 13 protein-coding genes (PCGs), 2 ribosomal RNAs (rRNAs), 22 transfer RNAs (tRNAs), and 2 non-coding regions (D-loop 1, D-loop 2). The overall base composition of D. major was G + C: 47.5%, A + T: 52.5%, apparently with a slight AT bias. Phylogenetic analysis showed that D. major was closely related to Dendrocopos leucotos.